On the uniform summability of the Fourier-Laplace series on the sphere - Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik; Abdul Sathar, Mohammad Hasan (Institute of Physics Publishing, 2020)
Convergence problems has been the focus of interest for researchers that are working in the fields of spectral theory. In the current research we investigate issues relating to the summability of the Fourier-Laplace series on the unit sphere. The necessary conditions which are required to obtain good estimation for summability of the Fourier-Laplace series investigated. This research will also provide new and sufficient conditions in the form of theorems and lemmas which will validate the uniform summability of the Fourier-Laplace series on the sphere.